2000
DOI: 10.1212/wnl.54.1.227
|View full text |Cite
|
Sign up to set email alerts
|

The value of pelvic thrusting in the diagnosis of seizures and pseudoseizures

Abstract: We evaluated pelvic thrusting as a potential diagnostic sign and localizing indicator of ictal onset. By reviewing the video-EEG results of patients with temporal lobe epilepsy, frontal lobe epilepsy, generalized epilepsy, and pseudoseizures. Pelvic thrusting occurred in 4% of right and 2% of left temporal lobe epilepsy patients, in 24% of frontal lobe epilepsy patients, and in 17% of patients with pseudoseizures. Pelvic thrusting is relatively common in frontal lobe epilepsy and in pseudoseizures, but also oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 8 publications
2
38
0
3
Order By: Relevance
“…The difference was not statistically significant 22. In two uncontrolled studies, flailing or thrashing movements were observed in 18% and 19% of the patients with PNES 28 29. We therefore did not find sufficient evidence to suggest that the presence of flailing or thrashing movements can distinguish PNES from ES.…”
Section: Resultsmentioning
confidence: 73%
“…The difference was not statistically significant 22. In two uncontrolled studies, flailing or thrashing movements were observed in 18% and 19% of the patients with PNES 28 29. We therefore did not find sufficient evidence to suggest that the presence of flailing or thrashing movements can distinguish PNES from ES.…”
Section: Resultsmentioning
confidence: 73%
“…Pelvic thrusting is most often seen in psychogenic seizures, but it has also been reported in frontal lobe seizures, sometimes combined with limb thrashing as part of hypermotor seizures, and less frequently in TLE. 5 Not all complex movements in TLE were of high amplitude: other patients displayed less violent and disorganized movements, such as repetitive body rocking. However, they were clearly distinct from typical automatisms and seemed unusual in the context of TLE.…”
Section: Resultsmentioning
confidence: 99%
“…Os movimentos pélvi-cos, embora tenham ocorrido em apenas 9 pacientes (19,1%), predominaram no sexo feminino (77,8%) 6,15,19 . Esta predominância foi evidenciada nos estudos realizados em portadores de epilepsias de lobo frontal, seguido das CNE 28 .…”
Section: Discussionunclassified